Components of Diesel Exhaust Particles Diversely Enhance a Variety of Respiratory Diseases Related to Infection or Allergy: Extracted Organic Chemicals and the Residual Particles after Extraction Differently Affect Respiratory Diseases - Takano, Hirohisa (the Society for Free Radical Research Japan, 2007)
Experimental and epidemiological studies have reported that diesel exhaust particles (DEP) can aggravate a variety of respiratory diseases including infection or allergy. However, the responsible components in DEP for the enhancement have not been identified. The present review demonstrates the different effects of the components of DEP on the respiratory diseases related to infection or allergy. We exposed mice to the organic chemicals (DEP-OC) and the residual carbonaceous nuclei (washed DEP) derived from DEP in the presence or absence of bacterial endotoxin (lipopolysaccharide: LPS) or allergen. In our first series of experiments, washed DEP combined with LPS synergistically exacerbated lung injury, which was concomitant with the enhanced lung expression of proinflammatory cytokines and chemokines, whereas DEP-OC combined with LPS did not. In contrast, our second series of experiments showed that DEP-OC, rather than washed DEP, enhanced allergen-related eosinophilic inflammation and proliferation of goblet cells in the airway epithelium, which was paralleled by the enhanced lung expression of eotaxin and interleukin-5. However, washed DEP with ovalbmin showed less change and increased the lung expression of interferon-γ. It is suggested that DEP components diversely affect various types of respiratory diseases, while the combination of organic chemicals and carbonaceous nuclei (whole DEP) mostly aggravate respiratory diseases.